Island of Glass - Roberts, Nora (New York : Berkley, 2016)
"As the hunt for the Star of Ice leads the six guardians to Ireland, Doyle, the immortal, must face his tragic past. Three centuries ago, he closed off his heart, yet his warrior spirit is still drawn to the wild. And there's no one more familiar with the wild than Riley-- and the wolf within her. An archaeologist, Riley is no stranger to the coast of Clare, but now she finds herself on unsure footing, targeted by the dark goddess who wants more than the stars, more than the blood of the guardians"--
Keywords: Stars -- Fiction; Time travel -- Fiction; Soldiers -- Fiction; Women archaeologists -- Fiction; Werewolves -- Fiction; Mermaids -- Fiction; Wizards -- Fiction; Prophets -- Fiction; Shapeshifting -- Fiction; Psychic ability -- Fiction; Man-woman relationships -- Fiction; FICTION / Romance / Contemporary; FICTION / Romance / Paranormal; Ireland -- Fiction; Fantasy fiction; Science fiction; Romance fiction